Development and morphology of the gynoecium and nutlet in two South-American Bulbostylis (Cyperaceae) species - González, Ana María (2010)
The anatomy and ontogeny of the gynoecium and nutlets of two Bulbostylis species with different micro-morphology, Bulbostylis capillaris sensu Barros and B. major, were analyzed. The specific aim of this work was to identify which part of the pericarp determines the differences in the nutlet surface between these two species. We found that pre-fertilization development is the same in both species, with differences between species appearing only after fertilization. In the nutlet of B. major, the exocarp forms a tuberculate primary sculpture that has nipple-like protuberances consisting of one conoidal silica body per cell, whereas the secondary sculpture is micro-granulose and is constituted by the cuticle. In the nutlet of B. capillaris, the primary sculpture is granulose and is formed by the presence of starch granules in the exocarp that do not degrade, whereas the secondary sculpture is smooth. © 2009 Elsevier GmbH. All rights reserved.